2019
DOI: 10.1111/ejss.12757
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of soil organic carbon stocks are larger under plastic film mulching for maize

Abstract: To determine the effect of plastic film mulching (FM) on changes in soil organic carbon (SOC) stocks, the annual C balances were determined by analysing the net ecosystem C budget (NECB), which means the difference between total C input and output, under FM and with no mulching for 2 years. Plots with black FM and no mulching were installed as the main treatment, and chemical and organic fertilizer plots were placed within each main plot as sub‐treatments. In the organic fertilizer treatment, a mixture of barl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Our results showed that plastic film mulch significantly reduced surface (0–20 cm) SOC content and concentration (Table 1), which is in accordance with other studies (Huo et al, 2017; Luo et al, 2015a, 2015b). This may be due to (a) microbial activity stimulation accelerating the decomposition of soil organic matter under plastic film mulch (Li et al, 2014) and (b) plastic film mulch increasing carbon loss in soil from respiration (Lee, Hwang, Park, Lee, & Kim, 2019). Current SOC levels on the Loess Plateau are lower than in other regions in China, including managed (e.g., farmland) and unmanaged (e.g., desert land) soils (Yang, Mohammat, Feng, Zhou, & Fang, 2007; Yu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that plastic film mulch significantly reduced surface (0–20 cm) SOC content and concentration (Table 1), which is in accordance with other studies (Huo et al, 2017; Luo et al, 2015a, 2015b). This may be due to (a) microbial activity stimulation accelerating the decomposition of soil organic matter under plastic film mulch (Li et al, 2014) and (b) plastic film mulch increasing carbon loss in soil from respiration (Lee, Hwang, Park, Lee, & Kim, 2019). Current SOC levels on the Loess Plateau are lower than in other regions in China, including managed (e.g., farmland) and unmanaged (e.g., desert land) soils (Yang, Mohammat, Feng, Zhou, & Fang, 2007; Yu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies demonstrate that plastic‐film mulching maintains or improves the SOC level via high root biomass or litter input to soils as the crop productivity increases (Wang et al, 2016a; Zhang, Zhang, Li, Yang, & Li, 2017). In contrast, some studies have found plastic‐film mulching significantly decreased SOC in croplands (Lee, Hwang, Park, Lee, & Kim, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…Many previous studies demonstrate that plastic-film mulching maintains or improves the SOC level via high root biomass or litter input to soils as the crop productivity increases (Wang et al, 2016a;Zhang, Zhang, Li, Yang, & Li, 2017). In contrast, some studies have found plastic-film mulching significantly decreased SOC in croplands (Lee, Hwang, Park, Lee, & Kim, 2019). This paper compares crop productivity, SOC, and soil moisture in alfalfa pasture converted cropland (RC) and continuous cropland (CC), both under plastic-film mulch, and under two regimes: fertilization and non-fertilization in the semiarid Loess Plateau over a 9 year period.…”
mentioning
confidence: 99%
“…In fact, this is premature senility rather than precocity. The main reasons are as follows: (1) extreme changes of high soil temperature and low temperature (Yin et al, 2016); (2) soil temperature in the exuberant growth period (flowering to filling stage) of maize reached above 40 • C with annual mulched new plastic, which is significantly higher than the appropriate temperature threshold of 35 • C for the normal growth and development of maize roots, and harmed maize root activity and caused premature senescence (Tao et al, 2013); (3) large amount of plastic input consumed the excessive soil water and nutrients, which caused soil microenvironment deterioration (Lee et al, 2018;Wang et al, 2020); and (4) annual mulched new plastic increased soil temperature, which led to the rapid growth of maize in the early stage and more consumption of nutrients and water, resulting in the phenomenon of lack of water and fertilizer in the late growth stage of maize (Bu et al, 2013). In this study, NM treatment can mitigate the above drawbacks, such as (1) achieve plastic reduction input and reduce the potential risk of overinvestment in plastic; (2) optimize the hydrothermal effect of soil and reduce the extreme high soil temperature, especially retained soil moisture during the fallow period, in this study; (3) effectively coordinated water demand contradiction of maize at early and late stages and created a more optimal water balance for maize growth, in this study; (4) this might be because NM treatment prolonged the maize growth period, delayed the functional period of green leaf, increased the leaf area index, and enhanced the accumulation and transformation of the photosynthetic product (Yin et al, 2020c); (5) no tillage with residual plastic film mulch may promote chlorophyll synthesis and increase photosynthesis of leaves via enhancing soil moisture conservation (Yang et al, 2018); and (6) this could partly be attributed to the increased transport of dry matter to the grain from the leaves, stems, and sheaths across the late maize growth stage.…”
Section: Grain Yield and Economic Benefit As Affected By Plastic Mulched Managementmentioning
confidence: 99%